Quality of Independent Expert Reports Used in Australian Takeovers - Paul Mazzola; Dionigi Gerace; Adam Reich (Australasian Accounting, Business and Finance Journal, 2020)
In this article, the authors investigate whether there has been an improvement in the quality of independent expert reports following ASIC's revisions to RG111 and RG112. These revisions include additional disclosures on the valuation methodologies used and explanation if the valuation was materially different from the company's recent trading price. It was expected that these revisions have led to an improvement in report quality where quality is determined by the accuracy of the expert's valuation. Results show that after the 2011 revisions, valuations became more accurate based on updated measures of report quality. However, experts with higher fees did not provide higher quality reports on average. The ﬁndings indicate that the independence provisions within the new rules were effective. Furthermore, they warn commissioning firms that higher fees are not necessarily indicative of higher quality reports.
Keywords: Corporate Regulations; Share Valuation; Mergers and Acquisitions